Establishing the College of Pathologists of East, Central and Southern Africa – The Regional East Central and Southern Africa College of Pathology - Shahin Sayed (African Journal of Laboratory Medicine, 2020)
Issues: The scarcity of pathologists in sub-Saharan Africa is a well established fact that is attributable to few training programmes in the region; this is further compounded by the lack of harmonised curricula, training and exams within and without member countries.